Has financial liberalization improved economic efficiency in the Republic of Korea? Evidence from firm-level and industry-level data - Jungsoo Park; Yung Chul Park (Asian Development Bank Institute (ADBI), 2014)
This study analyzes the effects of financial liberalization on the lending behavior of banks and non-bank financial institutions (NBFIs) before and after the 1997 Asian financial crisis, using panel regressions on Republic of Korea firm-level and industry-level data of the period 1991 - 2007. It also develops a financial liberalization index to incorporate the multifaceted nature of financial reform. Findings show that financial liberalization has led banks and NBFIs to allocate more of their loans to small and medium-sized firms with good performance histories, thereby helping these entities to improve their total factor productivity growth. This paper does not find similar effects of financial liberalization on efficiency at large firms or at the industry level. Heavier reliance on direct financing after the crisis has not improved the productivity of large firms.
Keywords: G20; O40; 330; financial liberalization; economic efficiency; banking; external finance